Social life of masks: Experience from Bangladesh - Zaman, Shahaduz; Matin, Imran; Shatil, Tanvir; Hossain, Faruq (BIGD, 2024)
The framework of masks’ social life is critical in numerous ways to understanding people’s behaviour concerning public health issues by providing a nuanced understanding of the use of masks in the community from a multi-dimensional socio-cultural perspective. This explores people’s attitudes towards public health measures, current practices, and the barriers to following them. This study aims to conduct explorative research to obtain a deeper understanding of the performance of masks as a material in society. It focuses on (a) how masks acquire meanings in different contexts throughout their lifetime and (b) how masks affect people’s behaviour in society. Two communities, namely Shibganj Upazila from Chapainawabganj District and Bhaluka Upazila from Mymensingh District, were selected for data collection. The anthropological study uses a set of qualitative techniques, including observation, in-depth interviews (35), key informant interviews (24), focus group discussions (15), and testimonies on masks (20) to collect data. The study finds the framework of the “social life of things” useful in many ways to deeply understand different local dynamics and contexts related to mask use in Bangladesh. For example, the study finds that people are not merely concerned with compliance or non-compliance with masks but also concerned with many other attributes of masks, such as fabric, colour, design, fashion, and the quality of the mask, since masks are associated with people’s social lives in various ways. Moreover, the study uncovered some ways of promoting mask use in public spaces. This includes providing free masks; delivering messages on mask-wearing in various ways, both verbally and using HBCC materials, and engaging local elites in mask-promoting activities.